Penyelesaian Sengketa Waris Melalui Mediasi Adat Dalihan Natolu - Camalia, Tamarine; Kusmayanti, Hazar; Mantili, Rai (Postgraduate Program in Law, Universitas Pattimura, 2024)
Introduction: The principle of Dalihan Natolu regulates three important aspects of vertical relationships between descendants, horizontal relationships between siblings, and relationships with the wider community. Dalihan Natolu reflects three important pillars, namely Hula-hula (in-laws), Dongan Sabutuha (brothers), and Boru (daughters).Purposes of the Research: The purpose of this article is to the settlement of inheritance disputes can be pursued through customary mediation using the Dalihan Natolu customary principle.Methods of the Research: This research is a normative legal research, namely legal research to examine a norm, principle and/or legal doctrine.Results of the Research: The results of the research obtained are as follows: First, the process of resolving inheritance disputes through Dalihan Natolu customary mediation emphasizes the value of deliberation and local wisdom. In practice, Dalihan Natolu functions as a mediator who creates conducive dialog conditions between the disputing parties, involving three important elements: Hula-hula, Dongan Sabutuha, and Boru. Second, the legal position of the Dalihan Natolu customary mediation decision in inheritance disputes has an important role both socially and culturally. Although this mediation decision does not have formal legal force, it is respected by indigenous people and serves as a strong moral basis.